Vitiligo and depression: an observational study in patients attending tertiary care centre - Katroliya, Preetam Singh; Vyas, Devesh; Argal, Deepak; Patel, Nishant (International Journal of Research in Medical Sciences, 2024)
Background: Vitiligo, a chronic skin disorder characterized by depigmentation and white patch formation, not only poses a cosmetic challenge but also imposes a significant psychological burden. The relationship between vitiligo and depression remains underexplored, despite growing recognition of their potential association. This observational study aimed to investigate the prevalence of depression and assess the quality of life (QoL) among patients with vitiligo attending a tertiary care center. Methods: A cross-sectional study was conducted at the dermatology and psychiatry departments of SRVS Medical College, Shivpuri, involving 150 vitiligo patients aged 18 to 60 years. Participants were assessed using the patient health questionnaire (PHQ-9), vitiligo area scoring index (VASI), and dermatology life quality index (DLQI). Statistical analyses were performed using statistical package for the social sciences (SPSS) version 26. Results: The mean age of participants was 38.55±14.82 years, with 69.3% being female. Nonsegmental vitiligo accounted for 84% of cases, and 42.6% had active disease. The mean DLQI score was 8.45±6.12, with female gender and active disease significantly associated with lower QoL scores. A strong correlation was observed between depressive symptoms and impaired QoL (DLQI). The prevalence of depression (PHQ-9 score ≥9) was 14.6%, with employed individuals showing a significantly higher prevalence compared to other groups. Conclusions: Our findings highlight the significant burden of depression and impaired QoL among vitiligo patients attending a tertiary care center. Addressing the psychosocial aspects of vitiligo alongside its dermatological manifestations is crucial for optimizing patient care and enhancing overall well-being. Further longitudinal research is warranted to elucidate the complex relationship between vitiligo and depression.